The Didactical Design of Fractions Addition Operation Using RME - Gantina, Inggrit; Herman, Tatang (International Conference on Elementary Education, 2020)
This research is motivated by the emergence of students' learning barriers in acquiring the concept of fractions mathematics. The purpose of this research is to explore learning obstacles in order to formalize a didactic scheme of mathematics learning on the concept of fractions addition operations which is applied in class V of elementary school. The method used in this study is DDR (Didactical Design Research) which is designed to provide advantages in considering the learning process regarding fractions addition operations through hypothetical learning trajectory (HLT) analysis based on realistic mathematic educations (RME). Participants in the research were 50 students consisting of 21 male and 29 female students of class V from one of the state's elementary schools in Sumedang. Learning activities are accomplished by confronting students with real life contexts until they are able to represent the concept of rational numbers addition operations. The results showed that the design of didactic design using the realistic mathematic educations (RME) approach can bring students from concrete situations to more formal situations so that most students were able to achieve the stated learning goals